Nicorandil: from ulcer to fistula into adjacent organs. Issue 2 (28th March 2012) - Trechot, Philippe; Petitpain, Nadine; Guy, Claire; Pinzano, Astrid; Javot, Lucie; Schmutz, Jean Luc; Marie, Béatrice; Barbaud, Annick
Abstract : Nicorandil is an original vasodilatator used to control angina by decreasing cardiac preload and afterload. Since 1997, many reports of single or multiple nicorandil‐induced ulcerations have been published. To date, eight cases of nicorandil‐induced fistula into adjacent organs have been described. The pathogeneses of nicorandil‐induced ulceration and fistula into adjacent organs are not yet elucidated. The two main hepatic biotransformation pathways of nicorandil are denitration and reduction of the alkyl chain leading to nicotinamide and niconitic acid which merge into the endogenous pool of nicotinamide adenine dinucleotide/phosphate. This merging which is known as saturable, may contribute to a slow and abnormal distribution of nicotinamide and nicotinic acid out of the endogenous pool. Under these special conditions, providing these two molecules in situ, nicotinic acid associated with nicotinamide may ulcerate rather recent or maintained trauma. Ulcers and fistulae induced by nicorandil heal after withdrawal. Surgical intervention is unnecessary and inappropriate as it is ineffective and exacerbates morbidity. All practitioners should be correctly informed about these serious but preventable nicorandil side effects, which mostly occur in the elderly and fragile population. In the absence of corrective measures, withdrawal of this original and active drug should be considered.